Association between neutrophil-lymphocyte ratio and viral load with opportunistic pulmonary infections in human immunodeficiency virus/acquired immunodeficiency syndrome patients - Pratikto, Bella C.; Suryana, Ketut (International Journal of Advances in Medicine, 2023)
Background: Acquired immunodeficiency syndrome (AIDS) is a syndrome of an opportunistic infectious disease due to decreased immune system by human immunodeficiency virus (HIV) infection. Neutrophil-lymphocyte ratio (NLR) and viral load were used to assess inflammatory status and the amount of HIV virus in the blood. This study aims to determine the association between NLR and viral load in HIV/AIDS patients with the opportunistic pulmonary infections. Methods: This study is an analytic observational study with a cross-sectional design. Data was collected through the medical records of HIV/AIDS patients at Wangaya General Hospital from January 2018 - April 2023. The data analysis method used was the Chi square test as bivariate tests. Results: A total of 139 subjects, the majority of HIV/AIDS patients who had opportunistic pulmonary infections were Balinese ethnicity (45.3%), female (37.6%), age ≥36 years old (54.7%), used ART for ≥3 months (41.5%), viral load <40 copies/ml, NLR ≥2.81 (47.9%), had adherence (43.7%), types of ART were used combination of tenofovir lamivudine efavirenz (45.2%), and private employed (42.5%). A statistically significant association was found between age with opportunistic pulmonary infections (p=0.003; PR=3.082; 95% CI=1.516-6.266). NLR showed a significant association with the incidence of opportunistic pulmonary infections (p=0.003; PR=8.274; 95% CI=1.838-37.249). This study also showed pulmonary tuberculosis (42.37%) as the most common opportunistic pulmonary infections. Conclusions: There is a significant association between NLR levels in HIV/AIDS patients with opportunistic pulmonary infections at Wangaya General Hospital, which the higher NLR levels correlates with higher opportunistic pulmonary infections.